Three-dimensional exploration of the chicken embryo, a comparative study of light sheet and histological visualisation. - M W Smallridge; T E Aktepe; M J C Coppo; P K Vaz; A Diaz-Méndez; C M Murray; G Segal; J M Devlin; C A Hartley (PLoS ONE)
Ultramicroscopy has offered new avenues into the visualisation of tissues within animal models, providing three-dimensional visualisation through the use of light sheet fluorescence microscopy. This study aimed to develop and apply an optical tissue clearing method to investigate the application of light sheet fluorescence microscopy to image late-stage chicken embryos, and compare anatomical visualisation to traditional histological staining. Seventeen-day old specific pathogen free embryos were collected, fixed, and sectioned. Haematoxylin and eosin stained sections were prepared for histology, while light sheet imaging required the tissues to be optically clear. For this, an ethyl cinnamate-based method was utilised, allowing for acquisition of clear, unobstructed three-dimensional images of significant organ structures and systems using only autofluorescence. The use of established histological techniques provided anatomical mapping of structures between familiar histology images and the three-dimensional light sheet images. Rendering of organs using light sheet imaging provided contextual insights into the surrounding tissues and physiological architecture of major organ structures and systems. This was most apparent through the identification of the pulmonary vein and rendering of a volumetric projection of the vasculature branching within the lung and the subsequent merging of vasculature into the left side of the heart. Overall, the visualisation of the chicken embryo was enhanced by combining traditional histology with the information gained by three-dimensional light sheet fluorescence microscopy.